Chemistry Craft and Entrepreneurship Practicum Module Based on Semi-Solid Preparations as a Learning Resource for High School Students - Luthfiana Dewi; Laili Nailul Muna (Jurnal Pendidikan Kimia Indonesia, 2022)
The learning activities applied are still dominated by textbooks, so additional learning resources are needed to support more creative and innovative learning activities. This study aims to create a semi-solid preparation-based chemical practicum module for craft and entrepreneurship (PKWU) as a learning resource for SMA/MA students. The type of research used is development research (R&D) with the 4D development model. The research subjects included one material expert, a media expert, four reviewers, and ten SMA/MA MIPA students. Quality assessment was carried out using a Likert scale questionnaire sheet and a Guttman scale questionnaire. The analysis technique uses quantitative and qualitative analysis. The results of the assessment show that material experts are 90.77% in the Very Good category, product ratings by media experts are 96.7% in the Very Good category, and the reviewer's assessment (chemistry teacher) gets an average score of average with a percentage of 90.25% in the Very Good category. The results of student responses to the module show a percentage of 95%. The results show that the PKWU practicum module based on semisolid preparations is feasible to use as an alternative learning resource in increasing student understanding. This research implies that teachers are expected to be able to use practicum modules that can facilitate students in carrying out practicum activities.